2018
DOI: 10.1021/acssuschemeng.8b02405
|View full text |Cite
|
Sign up to set email alerts
|

High Performance Cathode Recovery from Different Electric Vehicle Recycling Streams

Abstract: For environmental and sustainability reasons, spent Li-ion batteries must be recovered and recycled so that the full promise of an electrified future is realized. Li-ion battery recycling streams pose a serious challenge to all existing recycling technologies because of their unknown and diverse chemistry. In the work described in this paper, four representative recycling streams were used to demonstrate the flexibility of the recycling process developed at Worcester Polytechnic Institute (WPI) to accommodate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 25 publications
0
28
0
Order By: Relevance
“…In the process patented by Rockwood Lithium, Li is recovered from the mother liquor via electrodialysis or membrane separation [125]. Starting from sulfuric acid leaching liquor obtained similar to Zou et al [43], Gratz et al [85] and Zheng et al [126] applied purification process and element doping to obtain enhanced performance NMC (111). Zheng et al's process flowchart is shown in Figure 10.…”
Section: Sulfate Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…In the process patented by Rockwood Lithium, Li is recovered from the mother liquor via electrodialysis or membrane separation [125]. Starting from sulfuric acid leaching liquor obtained similar to Zou et al [43], Gratz et al [85] and Zheng et al [126] applied purification process and element doping to obtain enhanced performance NMC (111). Zheng et al's process flowchart is shown in Figure 10.…”
Section: Sulfate Systemmentioning
confidence: 99%
“…After adjusting the Co:Ni:Mn molar ratio to be 1:1:1, Ni 1/3 Mn 1/3 Co 1/3 (OH) 2 was co-precipitated using NaOH and NH 4 OH as alkaline/complexing agent for 48 h at pH 11 and a controlled temperature of 60 • C. Zheng et al reported the results of four 7-day campaigns, where four 30 kg samples of blended spent LIBs with different proportions of LIBs types (LCO, NMC, LMO, LCO, LFP) were processed in a pilot-scale laboratory set-up [126]. The resulted solid Ni 1/3 Mn 1/3 Co 1/3 (OH) 2 products served as precursor for resynthesizing NMC after mixing with 5% excess Li 2 CO 3 and sintering at 450 • C and 900 • C. The obtained active material presented a d 50 from 10 to 14 µm and an electrochemical capacity ranging from slightly over 140 mAh/g to 152 mAh/g at C/5 [126]. These publications are part of process development and commercialization of a LIB recycling pilot plant for Battery Resourcers Inc (Worcester, MA, USA).…”
Section: Sulfate Systemmentioning
confidence: 99%
“…Hydrometallurgical process steps are capable of producing high product purities. However, plants for counter-flow are larger than those used in pyrometallurgy and require a larger financial investment volume for their construction [21,48,49]. In general, important challenges are to achieve the demanded high recovery rates and, at the same time, high material purities.…”
Section: Mechanical-hydrometallurgical Recycling Technology and Challmentioning
confidence: 99%
“…Among other things, a process was developed in which, depending on the active material, 85 to potentially over 95% of the lithium can be recovered by mechanical (includes drying step) and hydrometallurgical means (leaching and subsequent precipitation of the lithium). pyrometallurgy and require a larger financial investment volume for their construction [21,48,49]. In general, important challenges are to achieve the demanded high recovery rates and, at the same time, high material purities.…”
Section: Mechanical-hydrometallurgical Recycling Technology and Challmentioning
confidence: 99%
“…Accordingly, the anode chemistry in this black mass contains 66.4% LCO and 33.6% NMC. Most of the current recycling processes are selective for one battery chemistry type, however a significant number of processes under development aim to handle cathode chemistry mixtures (Barik et al, 2017;Li et al, 2018;Zheng et al, 2018;Zou et al, 2013). This characterization technique successfully identified the NMC and LCO battery chemistries, and would also be able to detect NCA, LMO and LFP chemistries.…”
Section: Identification Of Lib Componentsmentioning
confidence: 99%